Comparison of the Nutrition on Different Fats on Lipid Profile, and Some Biochemical Parameters and their Relationship with Liver and Kidney Function in Male Rats - Batoul Khalaf Mohammed Al-Bayati; Wahbi Abdul Qadir Salman Al-Hamdani (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted on forty-nine healthy male albino males rats, from 1/11/2019 to 12/30/2019 fortwo months in the animal house of the College of Veterinary Medicine - University of Tikrit, their agesranged from 3-4 months and weights of 250-350 g current study aimed to determine the effect of nutritionon the different types of fat in the levels of blood lipids, kidney function, and liver enzymes. The resultsshowed a significant increase with a level of 0.05 (p?) in blood sugar concentration in the two groups ofanimal fat and vegetable oil group with a concentration of 8% g / kg of diet, and the two olive oil groupsdid not show significant differences compared to the control group. Levels of cholesterol, triglycerides, lowdensity lipoproteins, and very low-density lipoproteins in a group that was given fat animal by 8% g / kg ofdiet and a significant decrease in the group of olive oil by 4% g / kg of diet, significant increase (p? 0.05) inthe concentration of high-density lipoproteins in the two groups that have been treated with Olives oil by:4% and 8% g / kg, respectively. There were no significant differences in the rest of the other study treatmentscompared to the control group, and a significant increase of (p?0.05) in the concentrations of urea, creatinineand uric acid in the animal fat group by 8% g/kg of the diet, and a significant decrease in the group that wastreated with olive oil. As for the liver enzymes activity ALT, AST, and ALP there was a significant increase(p? 0.05) in the group that was treated as animal fat by 4% g / kg of diet, while we did not observe significantdifferences in the group that was treated with olive oil by 4% g / Kg of diet compared to a control group.